Nomophobia in adolescents based on gender: a case study of East Jakarta, Indonesia - Sagita, Dony Darma; Santika, Fatma (International Journal of Research in Counseling and Education, 2020)
Nomophobia is a modern phobia that occurs mostly in adolescents due to addiction to the use of a smartphone. The purpose of this study is to analyze the differences in the level of nomophobia among adolescents based on gender. This is a quantitative research with a comparative descriptive approach. Data were obtained from 400 adolescents selected using the convenience sampling technique. Furthermore, the instrument used was the Indonesian version of the Nomophobia Questionnaire (NMP-Q) consisting of 20 valid items with alfa Cronbach of 0,93 developed and adapted by Rangka et al. (2018). While hypothesis testing was carried out using the Independent Sample t-Test formula. The results showed a significant difference between nomophobia in boys and girls, with a t-value of -5.531 at a significance level (p) of 0.000. This means that in east Jakarta, the girls have higher nomophobia than men due to their significant inability to community effectively and efficiently while using their smartphones.